(8x 2 −15x)−(x 2 −27x)=ax 2 +bxleft parenthesis, 8, x, squared, minus, 15, x, right parenthesis, minus, left parenthesis, x, squ
quester [9]
Answer:
<h2>5</h2>
Step-by-step explanation:
Given the expression (8x² −15x)−(x² −27x) = ax² +bx, we are to determine the value of b-a. Before we determine the vwlue of b-a, we need to first calculate for the value of a and b from the given expression.
On expanding the left hand side of the expression we have;
= (8x² −15x)−(x² −27x)
Open the paranthesis
= 8x² −15x−x²+27x
collect the like terms
= 8x²−x²+27x −15x
= 7x²+12x
Comparing the resulting expression with ax²+bx
7x²+12x = ax²+bx
7x² = ax²
a = 7
Also;
12x = bx
b =12
The value of b - a = 12 - 7
b -a = 5
Hence the value of b-a is equivalent to 5
The first one is 156, the second 420 the third is 6,138 and the forth one is 64.
Since the second line is parallel to the first, it will have the same slope. The y-intercept of the new line is 4 (because of the coordinates given) so the equation of Lynda's second cut is y = 1/4x + 4 which is choice C
Answer:
a:36 b:30
Step-by-step explanation:
A:180-56, since it is a straight line.
180-124-20= 36
B:180-120=60
60+3x+1x=180
60+4x=180
4x=120
x=30
7 that is what t should be